A. HUBUNGAN PEMANFAATAN PERPUSTAKAANDENGAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN FIKIH DI MAN 1 PADANGSIDIMPUAN - Rina Rina Juliana (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
Library utilization is one learning resource that can add insight and information for learners. The problem raised in this research is whether there is a correlation between the utilization of learning resources with students' learning result in the field of Jurisprudence study in MAN 1 Padangsidimpuan? The benefits to be achieved by researchers is for teachers to be able to utilize the library as one source of learning in improving student learning outcomes. The purpose of this research is to know the correlation between the utilization of learning resources with the students' learning result in the field of Jurisprudence study at MAN 1 Padangsidimpuan. To achieve this goal, this research uses quantitative approach and correlational research type. Technique of collecting data through questionnaire and documentation.Validity test used pearson product moment correlation formula, while reliability test used alpha croanbach formula. To analyze the data used inferential descriptive method is by using simple correlation. The amount of correlation variable of library utilization with student learning result is 0,695 while contribution of variable X1 withY is 48,30% then rest 51,70% determined by other variable. Utilization of learning resources is closely related to student learning outcomes. This is because students have been able to identify, explore, investigate, guess, and finally find solusiterhadap problems that are given by teacher in field of fiqh study. Keywords: Utilization, Learning Resources, Learning Outcomes